Presence of Cocaine in the Tissues of the European Eel, Anguilla anguilla, Exposed to Environmental Cocaine Concentrations - CAPALDO, ANNA; GAY, FLAMINIA; Maddaloni M.; VALIANTE, Salvatore; DE FALCO, MARIA; Lenzi M.; LAFORGIA, VINCENZA (Water, Air, & Soil Pollution, 2012)
The presence of illicit drugs and their metabolites in surface waters has to be considered a new type of hazard, still unknown, for the aquatic ecosystem, due to the potent pharmacological activities of all the illicit drugs. Our research was therefore aimed at evaluating the impact of illicit drugs on the aquatic fauna, till now still undervalued. To this aim, we verified the ability of the European eel (Anguilla anguilla), a well-known biomonitor of environmental contamination, to bioaccumulate cocaine, one of the most abundant illicit drugs found in surface waters. Silver eels were exposed to a nominal cocaine concentration of 20 ng/l for one month; at the same time, control, carrier and post-exposure recovery groups were made. Brains, gills, liver, kidney, muscle, gonads, spleen, digestive tract and sections of dorsal skin were assayed by high-pressure liquid chromatography (HPLC). Cocaine was found in the tissues of the treated eels, and, at low concentrations, in almost all tissues of post-exposure recovery eels. These results indicate that cocaine is able to accumulate into the eel tissues; its presence suggests potential risks for eels, since cocaine could affect their physiology and contribute to their decline, and for humans, consuming contaminated fish